Reminding of risks of using water tankless WC and parameters of toilets and flush valves mentioned in BOQ - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the reminder about risks of using water tankless WC and parameters of toilets and flush valves mentioned in BOQ for BRACU new campus project.